PENGELOLAAN DESTINASI EKOWISATA di BALI UNTUK PARIWISATA YANG BERKELANJUTAN : STUDI LITERATUR - Ningrat, I Gusti Agung Diah Surya; I Gusti Ketut Indra Pranata; Ni Kadek Listya Apriliani; Ni Luh Candra Sihvani; I Putu Wahyu Mahardika Adinata; I Putu Gede Kori Pratama (UHN IGB Sugriwa Denpasar, 2026)
This study aims to analyze the patterns of ecotourism destination management in Bali through a synthesis of literature published between 2008 and 2025, and to formulate relevant strategies to strengthen sustainable tourism practices. The study is motivated by increasing environmental, social, and cultural pressures associated with tourism growth, necessitating management approaches that ensure a balance between ecological preservation and community well-being. A literature review method was employed by examining 25 scientific articles obtained through Google Scholar. The data were analyzed using a matrix that mapped the theoretical foundations, research contexts, characteristics, methods, and principal findings of each study. The results indicate that sustainable tourism theory and community participation constitute the dominant conceptual frameworks in ecotourism management in Bali. Local values such as Tri Hita Karana are shown to reinforce the integration of human, environmental, and spiritual dimensions within tourism activities. The findings also reveal several recurring challenges, including overtourism, gentrification, environmental degradation, and power asymmetries in governance structures. Furthermore, numerous studies highlight that collaborative governance models, particularly the pentahelix approach enhance the effectiveness of destination management. Based on the literature synthesis, recommended strategies include strengthening community capacity and participation, fostering cross-sectoral collaboration, enforcing regulations grounded in environmental carrying capacity, and integrating local wisdom throughout all stages of management. These strategies are expected to advance ecotourism practices that are equitable, resilient, and sustainable within the Balinese context. Keywords: ecotourism, sustainable tourism, community participation, Tri Hita Karana